The decline in support for penal welfarism. Evidence of support among the elite for punitive segregation - Cesaroni, Carla (The British journal of criminology, 2003)
Garland 2000; 2001 suggests that the liberal elite in the United Kingdom and the United States no longer sees itself as isolated from the everyday effects of crime. The result of this new experience of crime, he suggests, is that support among the liberal elite for punitive segregation is no longer lower than that of other citizens. In this paper, we look at Canadian evidence relevant to these two propositions. Data form national surveys are supportive of the analysis that David Garland presents for the decline in support for rehabilitative, reintegrative, or correctionalist crime control strategies